Institutional and legal mechanisms to promote accountability in Iran - Monavvarian, Abbas (Asian Review of Public Administration, 1991)
This article discusses institutional and legal mechanisms previously and presently existing in the Islamic Republic of Iran in enforcing accountability. Previously the author argues that, during the time of Sha, power and authority was only vested and concentrated in the hands of a few with no proper accountability. After the Islamic Revolution of 1979, there came about in Iran, a more proper and legal institutional mechanism for accountability based on the theory of Separation of Powers. Now, the President is accountable to the people who elected him, on the one hand, and the leader of the revolution and the Islamic Consultative assembly, on the other. Now, there is a clearer demarcation of executive, legislative and judicial powers which has to promote accountability. However, the author also argues that the existence currently in Iran of a strong centralised administrative and political structure does not augur well for accountability. He, thus, calls for more decentralisation of power and authority to the regions.